2014
DOI: 10.1016/j.ijme.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility, compromise and opportunity: Students' perceptions of balancing part-time work with a full-time business degree

Abstract: Amidst the growing importance of employability in higher education, this study explores and identifies the motivations behind full-time university students engaging in part-time employment during term time, how students cope with simultaneously managing the two activities and how part-time working influences their career aspirations. Semi-structured interviews are used to obtain data from a sample of 30 business degree students at a UK university.The findings confirm previous studies, that financial necessity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
4
35
0
Order By: Relevance
“…As this has not been investigated before, such findings have not been reported in extant studies. However, Evans et al (2014) reported that among UK students there seem to be a lack of connection between students working part-time and future career direction, albeit in a qualitative study. The present finding reporting self-efficacy (and gender) as strong predictors of career aspirations and part-time working in a non-Western context (Nigeria), can therefore be taken as tentative.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…As this has not been investigated before, such findings have not been reported in extant studies. However, Evans et al (2014) reported that among UK students there seem to be a lack of connection between students working part-time and future career direction, albeit in a qualitative study. The present finding reporting self-efficacy (and gender) as strong predictors of career aspirations and part-time working in a non-Western context (Nigeria), can therefore be taken as tentative.…”
Section: Resultsmentioning
confidence: 93%
“…Evans et al, 2014, Ford et al, 1995, Richardson et al, 2009), few have actually followed this up with finding out from students who do not work part-time, the reasons that underpin this decision (see for example, Hodgson and Spours, 2001). In this study, we asked students who do not work part-time, why they do not.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this is mostly seen to be financially driven (Richardson et al, 2009), part--time working can also help individuals 'try--out' future jobs (Billet and Ovens, 2007) and is therefore useful in supporting career aspirations. In addition, the students themselves perceive their part--time working as beneficial to their job prospects (Evans et al, 2014;Martin and McCabe, 2007;Morrison, 2009). However, the value placed by employers on students' part--time working remains relatively unexplored, highlighting a clear research gap.…”
Section: Introduction --Employability and The Needs Of Employersmentioning
confidence: 99%